2013
DOI: 10.3389/fendo.2013.00060
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neurodevelopmental Outcomes are Common in Children with Transient Congenital Hyperinsulinism

Abstract: Introduction: Neuroglycopenia is recognized to be associated with abnormal neurodevelopmental outcomes in 26–44% of children with persistent congenital hyperinsulinism (P-CHI). The prevalence of abnormal neurodevelopment in transient CHI (T-CHI) is not known. We have aimed to investigate abnormal neurodevelopment and associated factors in T-CHI and P-CHI.Materials and Methods: A cohort of children with CHI (n = 67, age 2.5–5 years) was assessed at follow-up review and noted to have normal or abnormal (mild or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 17 publications
4
99
4
5
Order By: Relevance
“…Since the early 1960s, researchers have shown that despite medical advances, the incidence of poor neurological outcome remains somewhere between 20 and 40% [1-4]. Transient forms of hyperinsulinism such as perinatal stress hyperinsulinism also occur and appear to carry similar risks of poor neurological outcome [3, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1960s, researchers have shown that despite medical advances, the incidence of poor neurological outcome remains somewhere between 20 and 40% [1-4]. Transient forms of hyperinsulinism such as perinatal stress hyperinsulinism also occur and appear to carry similar risks of poor neurological outcome [3, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…HC is an uncommon disorder of glucose metabolism, which is the most common cause of persistent hypoglycemia of the newborn [1][2][3] . Its pathogenesis lies in excessive production of insulin by pancreatic β cells, even with low blood glucose levels 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hyperinsulinism (HC) is the main cause of persistent and recurrent hypoglycemia in the first year of life [1][2][3] . Its incidence ranges from 1/27,000 to 1/50,000 in newborns 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study in Manchester, UK showed that abnormal neurodevelopmental outcome is common in children with transient congenital Hyperinsulinism. (9) In their study, they followed a cohort of children with CHI between ages 2.5-5 years and assessed whether they have normal or abnormal neurodevelopmental outcomes in the domains of speech and language, Vision and motor. Children were classified as having persistent congenital hyperinsulinism of infancy (P-CHI), if they had undergone surgery or remained on medical therapy, or transient congenital hyperinsulinism of infancy (T-CHI) if medical treatment for hypoglycemia was stopped.…”
Section: Managementmentioning
confidence: 99%